1990
DOI: 10.1002/jmv.1890300211
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of hepatitis B virus DNA polymerase by 3′‐fluorothymidine triphosphate and other modified nucleoside triphosphate analogs

Abstract: The 3'-fluoromodified nucleotide analogs 3'-fluorothymidine triphosphate (FdTTP), 2',3'-dideoxy-3'-fluoro-5-chlorouridine triphosphate (F-5CldUTP), 2',3'-dideoxy-3'-fluoro-5-ethyluridine triphosphate (F-5EtdUTP), 2',3'-dideoxy-3'-fluorouridine triphosphate (FdUTP), and 2',3'-dideoxy-3'-fluoro-5-fluorouridine triphosphate (F-5FdUTP) as well as 2',3'-dideoxythymidine triphosphate (ddTTP), 2',3'-didehydro-2',3'-dideoxythymidine triphosphate (ddeTTP), 3'-chlorothymidine triphosphate (CldTTP), and 3'-rhodanothymidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…For estimation of the HBV DNA polymerase activity, virus particles were pelleted from HBV DNA positive human sera and the endogenous DNA polymerase was assayed as described previously (Meisel et al, 1990). The reaction mixture (49 ILl)contained 42mM Tris-hydrochloride (pH 7.5), 34mM MgCI2, 340mM KCI, 22 mM 2-mercaptoethanol, 0.4% Nonidet P40, 70 ILM of the fourth one as labelled triphosphate.…”
Section: Endogenous Hbv Dna Polymerasementioning
confidence: 99%
“…For estimation of the HBV DNA polymerase activity, virus particles were pelleted from HBV DNA positive human sera and the endogenous DNA polymerase was assayed as described previously (Meisel et al, 1990). The reaction mixture (49 ILl)contained 42mM Tris-hydrochloride (pH 7.5), 34mM MgCI2, 340mM KCI, 22 mM 2-mercaptoethanol, 0.4% Nonidet P40, 70 ILM of the fourth one as labelled triphosphate.…”
Section: Endogenous Hbv Dna Polymerasementioning
confidence: 99%
“…The DNA polymerase a, the de novo DNA-synthesizing enzyme (1), is almost insensitive toward the triphosphate of FddThd. Recently, it was found that the triphosphates of the other nucleoside analogs studied here, FddMeCyt and ddeThd, were equally effective and selective inhibitors of HBV DNA polymerase (14).…”
Section: Discussionmentioning
confidence: 88%
“…While a 50o inhibition of DNA polymerase p was measured at a concentration of 2.2 ,uM triphosphate of FddThd, the inhibitory concentration of the triphosphate in the DNA polyrnerase a assay was >200 ,uM. In contrast, reverse trans-criptase from human immunodeficiency virus is inhibited at a concentration of as low as 0.05 ,uM (12) -and the-polymerase from HBV is inhibited at 0.15 p.M (14). This means that the cellular DNA polymerase ,, which is primarily involved in DNA repair (1), is 45-fold less sensitive to inhibition by the compound than the human immunodeficiency virus reverse transcriptase is and 15-fold less sensitive than the HBV DNA polymerase is.…”
Section: Discussionmentioning
confidence: 98%
“…Meanwhile, however, 3'-azido-2',3'-dideoxythymidine has been shown to be unable to suppress duck HBV (DHBV) replication in vitro and in vivo (9,26) or to be effective against hepatitis B infections of AIDS patients coinfected with HBV (4). A series of compounds, such as 2',3'-dideoxy-3'-fluorothymidine 5'-triphosphate and some closely related 3'-fluoro-modified dTTP analogs, 2',3'-didehydro-2',3'-dideoxythymidine 5'-triphosphate, ddTTP, ddCTP, ddGTP, and 5-substituted dUTP derivatives, were likewise described as efficient inhibitors of human immunodeficiency virus RT (1,8,18,19,24), exhibiting promising effects on HBV DNA polymerase (20,25) or DHBV DNA polymerase (14,25). Of these agents, only the 2',3'-dideoxynucleosides have been examined for their antiviral efficiency in two different HBV-producing cell systems (3,13,26) or in DHBV-infected animals (11,13), with varying success.…”
mentioning
confidence: 99%
“…The sugar-modified nucleosides and their corresponding 5'-triphosphates were synthesized and purified by wellestablished procedures (10,12) (20). The reaction mixture (49 ,ul) contained 42 mM Tris-HCl (pH 7.5), 34 mM MgCl2, 340 mM KCl, 22 mM 2-mercaptoethanol, 0.4% Nonidet P-40, 70 ,uM concentrations each of three of the deoxynucleoside triphosphates and, on the basis of the inhibitor examined, a 0.7 ,uM concentration of the fourth one as a labeled triphosphate (this concentration varied between 0.22 and 1.18 ,M in kinetic studies) (64 kdpm/pmol).…”
mentioning
confidence: 99%